Preparing for Life in a Digital Age: The IEA International Computer and Information Literacy Study International Report - Fraillon, Julian; Ainley, John; Schulz, Wolfram; Friedman, Tim; Gebhardt, Eveline (Cham Springer Nature, 2014)
Assessment, Testing and Evaluation; Computers and Education; International and Comparative Education
English
Keywords: Humanities; Education; Information technology industries; Coins, banknotes, medals, seals (numismatics); Assessment, Testing and Evaluation; Computers and Education; International and Comparative Education